Analysis of Factors Affecting Income Smoothing of Sharia and Non-Sharia Stock Companies - Mardiani, Sari; Husni, Tafdil; Adrianto, Fajri (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the factors impacting income smoothing practices in both Sharia-compliant stock companies and non-Sharia stock companies. The study utilizes the Eckel index to calculate income smoothing. Among the findings, 116 Islamic stock companies and 43 non-Sharia stock companies were identified as engaging in income smoothing. The independent variables considered in this study include family ownership and tax avoidance, while firm size and leverage are used as control variables. The research employs panel data regression for data analysis. The study results reveal that the factors influencing income smoothing in Islamic stock companies are similar to those in non-Sharia stock companies, though they have differing effects. Family ownership exhibits a positive and significant impact on income smoothing in both Sharia and non-Sharia stock companies. However, tax avoidance has a positive and significant effect on income smoothing in Sharia stock companies, while it has the opposite effect on non-Sharia stock companies. As for the control variables, firm size does not significantly influence income smoothing in either type of company, and neither does leverage.